Variability in size and age at maturity in the marine scavenger Buccinanops globulosus (Gastropoda: Nassariidae) from Patagonia - Avaca, Maria Soledad (2015)
Growth rates and size-age at maturity are life history traits that combine in different ways to achieve maximal fitness. The marine scavenger Buccinanops globulosus was used as a model to explore the variation on female size-age at maturity and reproductive effort among three populations characterized by different growth rates (slow, moderate and rapid). This species constitutes the target of an artisanal fishery in North Patagonia. Here, a suite of different estimators of size-age at maturity derived from gonad histological analysis and the study of females carrying egg capsules were obtained. Data were modelled using a logistic function and the maturity patterns were compared among populations. We found that female size and age at maturity were variable and site-specific. The fastest-growing population showed the lowest reproductive effort. Slow and rapid-growing females mature at different sizes but at the same age whereas moderate-growing females mature both at a different size and age (intermediate size and at earlier age). Thus, results obtained here are difficult to reconcile with a single reaction norm for a single genotype in the studied populations. Growth rate variation is not enough to explain the patterns described here. The information provided could be used for the establishment of fishery management actions, such as minimum landing size.